Analisis Produksi Jagung dengan Penyertaan Dana Penguatan Modal Lembaga Usaha Ekonomi Pedesaan (Dpm-Luep) di Provinsi Sumatera Utara - Festaria, Ledy; Ginting, Rahmanta; Siregar, Muhammad Akbar (Universitas Medan Area, 2019)
Production is influenced by a combination of many factors including land area, fertilizer, distribution of varieties, labor and capital availability. This study aims to analyze whether the variable of land area, width of the spread of varieties and capital (DPM-LUEP) significantly influence the corn production in North Sumatra Province. The data used in this study used secondary data starting from 2011 to 2015. Secondary data consisted of data of land area, extent of distribution of varieties and capital grant (DPM-LUEP) in 7 (seven) Regency of corn production center. Secondary data is obtained from Food and Livestock Service Department of North Sumatera Province, Food Crops and Horticulture Agency and related Institution which is deemed appropriate. The method of analysis used in this study using multiple regression method. Based on the result of the research, it can be concluded that the overall model of maize production is estimated to give significant result, because independent variables are land area, area of spread of varieties and capital that is observed significant with real level Î± = 5%. The observed variables are compatible with their theoretical expectations.